2000
DOI: 10.1021/jm9905155
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine Inhibitors of Human Cytosolic Phospholipase A2

Abstract: Introduction. Phospholipase A 2 (PLA 2 ) is a group of lipolytic enzymes that catalyze the hydrolysis of fatty acid ester bonds at the sn-2 position of phospholipids. This enzyme is thought to play an important role in the biosynthesis of eicosanoids via the release of arachidonic acid from biomembranes. Another product from biomembranes, a lysophospholipid, is converted to plateletactivating factor (PAF) known as an inflammatory mediator. PLA 2 s have been generally classified into secretory PLA 2 (sPLA 2 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 18 publications
3
123
0
Order By: Relevance
“…In our studies with CHO-K1 and HEK293 cells, it is clear that essentially all of the released [ 3 H]arachidonate is accounted for by that which accumulates in the culture medium. Also the fact that the cPLA 2 -␣ inhibitors reduce accumulation of [ 3 H]arachidonate in the medium in the present as well as in previous studies (2,26,28,42) The data presented in this paper provide a particularly clear example of cross-talk between hGIIA or hGX and cPLA 2 -␣. A second clear example of this cross-talk comes from the recent study of Han et al (15).…”
Section: Localization Of Hgiia In Hek293 Cells By Immunofluorescence-supporting
confidence: 84%
“…In our studies with CHO-K1 and HEK293 cells, it is clear that essentially all of the released [ 3 H]arachidonate is accounted for by that which accumulates in the culture medium. Also the fact that the cPLA 2 -␣ inhibitors reduce accumulation of [ 3 H]arachidonate in the medium in the present as well as in previous studies (2,26,28,42) The data presented in this paper provide a particularly clear example of cross-talk between hGIIA or hGX and cPLA 2 -␣. A second clear example of this cross-talk comes from the recent study of Han et al (15).…”
Section: Localization Of Hgiia In Hek293 Cells By Immunofluorescence-supporting
confidence: 84%
“…Our research group has previously reported the incorporation of curcumin into A2B star polymer micelles and effectiveness of this preparation in glioblastoma [63,64]. A retention of curcumin's biological activity in nanocarriers, an enhanced permeability and retention (EPR) effect and diffusion of curcumin into the neighboring glioblastoma cells could provide an improved therapeutic intervention in vivo [65] Pyrrolidine-2 is an inhibitor of cPLA2a, a key rate limiting enzyme in the synthesis of eicosanoids and a necessary player in the formation of lipid droplets [66,67]. In normal brain tissues, particularly in astrocytes and microglia, excessive PLA2 activation in response to stressors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen, (E)-1-(4-(2-(N,Ndimethylamino)ethoxy)phenyl)-1,2-diphenylbut-1-ene, and nafoxidin, 1-(2-(P-(3,4-dihydro-6-methoxy-2-phenyl-1-naphtyl)phenoxy)-ethyl)pyrrolidine hydrochloride were obtained from Sigma. Pyrrolidine-1 was synthesized as previously described [48,49]. 1-palmitoyl-2-[1-14 C]arachidonyl phosphatidylcholine (PtdCho) (57 mCi/mmol) and 1-palmitoyl-2-[1-14 C]arachidonyl phosphatidylethanolamine (PtdEtn) (57 mCi/mmol) were from New England Nuclear.…”
Section: Methodsmentioning
confidence: 99%
“…To discriminate between secretory PLA 2 (sPLA 2 ) and intracellular PLA 2 -mediated arachidonic acid release, we employed the PLA2 inhibitors pyrrolidine-1, AACOCF 3 and BEL. Pyrrolidine-1 is a potent and selective inhibitor of cPLA 2 -α [48,49]. BEL is an inhibitor of iPLA 2 [56,57] whereas AACOCF 3 inhibits both cPLA 2 -α and iPLA 2 [56,58].…”
Section: Pcb-induced Arachidonic Acid Release In Human Platelets Is Mmentioning
confidence: 99%